Predictors of anemia among HIV-infected children in Ethiopia: systematic review and meta-analysis - Desalegn Girma; Zinie Abita; Wubetu Agegnehu; Daniel Asmelash; Amanuel Adugna; Nigusie Shifera; Melsew Setegn Alie; Gossa Fetene Abebe (Scientific Reports)
Abstract Anemia continues to be one of the common complications among HIV-infected children. In Ethiopia, though there is a systematic review and meta-analysis study on anemia among HIV-infected children, it only disclosed the effect Highly Active Antiretroviral Treatment on HIV/AIDS-anemia comorbidity, and yet, the meta effect of other potential factors such as type of ART, presence of opportunistic infection, advanced stage of HIV/AIDS, and cotrimoxazole therapy on HIV/AIDS-anemia comorbidity have not been explored in the previous review. Therefore, this systematic review and meta-analysis aimed to identify the factors associated with anemia among HIV-infected children. Moreover, this study provides an up-to-date pooled estimate of anemia among HIV-infected children in Ethiopia. We systematically searched PubMed, HINARI, Science Direct, Cochrane Library, Google Scholar, and African Journals Online on February 3, 2024, to identify relevant primary research articles. The Briggs Institute (JBI) Checklist was used to check the quality of the original studies. Meta package for proportions (Metapro) was used to estimate the pooled prevalence of anemia among HIV-infected children using the random-effects model. Heterogeneity across studies was checked using the I-square test. Funnel plots visual inspection and Egger’s tests were done to detect publication bias. The pooled prevalence of anemia among HIV-infected children in Ethiopia was 23.79% (95% CI 17.28, 31.81). Age < 7 years (OR 3.71, 95% CI 2.58; 5.33), advanced HIV disease (OR 2.78, 95% CI 2.00; 3.87), intestinal parasitic infection (OR 2.28, 95% CI 1.02; 5.09), poor ART treatment adherence (OR 1.96, 95% CI 1.23; 3.10), opportunistic infection (OR 2.81, 95% CI 1.59; 4.95), viral load > 1000 copies/ml (OR 4.29, 95% CI 2.28; 8.09), and zidovudine containing regimen (OR 5.07, 95% CI 2.41; 10.64) were identified as factors associated with a higher risk of anemia. Whereas, cotrimoxazole prophylaxis therapy (OR 0.49, 95% CI 0.35; 0.72) reduces the risk of anemia among HIV-infected children. In Ethiopia, anemia remains a public health concern among children living with HIV. Therefore, regular screening and management of anemia are important for HIV-infected children, particularly for those with advanced HIV disease, opportunistic infection, high viral load, and who are taking zidovudine-containing regimens for better clinical outcomes. Moreover, preventive chemotherapy (deworming) and counseling on infection prevention should be provided for children living with HIV to prevent parasitic infection.